2014
DOI: 10.1016/j.ajog.2013.10.609
|View full text |Cite
|
Sign up to set email alerts
|

576: Evaluation of the fetal QT interval using non-invasive fetal ECG technology

Abstract: Non-invasive fetal electrocardiography (NI-FECG) is a promising alternative continuous fetal monitoring method that has the potential to allow morphological analysis of the FECG. However, there are a number of challenges associated with the evaluation of morphological parameters from the NI-FECG, including low signal to noise ratio of the NI-FECG and methodological challenges for getting reference annotations and evaluating the accuracy of segmentation algorithms. This work aims to validate the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Zhu et al combined adult QT annotations from different individuals and automated algorithms in order to improve the estimation of the reference annotations. This algorithm has recently been used in Behar et al (2014e) to estimate foetal QT (FQT) by merging the annotations from three medical professionals (see figure 9). We recommend using a consensus of at least three human annotations for obtaining morphological references such as FQT interval particularly given that no open SECG segmentation and signal quality algorithm exists to date.…”
Section: Intermediate Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhu et al combined adult QT annotations from different individuals and automated algorithms in order to improve the estimation of the reference annotations. This algorithm has recently been used in Behar et al (2014e) to estimate foetal QT (FQT) by merging the annotations from three medical professionals (see figure 9). We recommend using a consensus of at least three human annotations for obtaining morphological references such as FQT interval particularly given that no open SECG segmentation and signal quality algorithm exists to date.…”
Section: Intermediate Conclusionmentioning
confidence: 99%
“…In recent years, a handful of NI-FECG commercial monitors have appeared in the market and more competing solutions are in development Particularly interesting are two monitors that have obtained FDA clearance: the Monica AN24 monitor (Monica Healthcare, Nottingham, UK) and the Meridian M100/M1000 monitors from MindChild Medical (North Andover, MA) 6 . Both monitors have proved to be accurate in detecting FHR (Sameni et al 2009, Reinhard et al 2012, and some seminal work on extracting morphological information has shown promise for the latter monitor (Clifford et al 2011, Behar 2014. However, the studies associated with these monitors were limited in patient numbers and population size and further research is needed to address a broad range of populations and conditions.…”
Section: Commercial Ni-fecg Monitorsmentioning
confidence: 99%
See 2 more Smart Citations